SYSTEM OF MANAGEMENT IN EFFICIENCY AND QUALITY OF MEDICAL CARE AT THE S. FYODOROV EYE MICROSURGERY FEDERAL STATE INSTITUTION - А. М. Chukhrayov (Офтальмохирургия, 2017)
The system of management in efficiency and quality of medical care, developed at the S. Fyodorov Eye Microsurgery Federal State Institution, provides a constant growth of quantitative and qualitative indicators of the medical activities of the Institution that ensures for patients receive high-quality ophthalmic care services. The developed organizational and methodological principles of management in efficacy and a quality of medical care, methods of audit, a reasoned approach to the organization and remuneration of medical staff may be useful in the practice of health care facilities of ophthalmic profile and other specialized areas of medicine.